Human Rights defense in a post conflict society: The colombian case - Molina Betancur, Carlos Mario (2016)
The defense of human rights in a post-conflict society is a great challenge for any civilized society.The post-conflict in Colombia must be a process that is addressed by the political and legal parameters of the Constitution in force in the country. Nevertheless, to guarantee a model social state of law based on respect for human dignity, work and solidarity of its members and the prevalence of general interest. Second, to provide legal security to the State, civil society and demobilized groups to the latter political and democratically participate in the governance of the state, with the horizon of their actions respect for human rights and thereby ensures that the damage caused to the victims is solved by the Truth, Justice and Reparation.